Life Lessons and Literary Works - Bakhronova Matluba Akhmedovna (Researchparks Publishing, 2022)
Each nation has its own way of thinking, worldview, cultural and spiritual concepts related to the development of medicine, life experience and traditions. The subject of illness is common in modern literature as a metaphor for mental disorders in the body or as a symbol of social ills. This article discusses the presentation and analysis of diseases in English and Uzbek literature based on the life lessons of writers, in particular, the creation of disease-related plots of writers such as U. Hoshimov, A. Kahhor, E.A. Poe, O’Henry.